Genetic and Systematic Approaches Toward G Protein-Coupled Abiotic Stress Signaling in Plants - Wu, Ting-Ying; Urano, Daisuke (Frontiers in Plant Science, 2018)
Heterotrimeric G protein, composed of Gα, Gβ and Gγ subunits, modulates plant adaptations to environmental stresses such as high salinity, drought, extreme temperatures and high light intensity. Most of these evidence were however derived solely from conventional genetics methods with which stress-associated phenotypes were compared between wild type and various G protein mutant plants. Recent advances in systematic approaches, mainly transcriptome and proteome, have contributed to in-depth understanding of molecular linkages between G proteins and environmental changes. Here, we update our knowledge on the roles of G proteins in abiotic stress responses. Furthermore, we highlight the current whole genome studies and integrated omics approach to better understand the fundamental G protein functions involved in abiotic stress responses. It is our purpose here to bridge the gap between molecular mechanisms in G protein science and stress biology and pave the way towards crop improvement researches in the future.